Simulation, modeling, and programming for autonomous robots : Third International Conference, SIMPAR 2012, Tsukuba, Japan, November 5-8, 2012. Proceedings - Noda, Itsuki (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the Third International Conference on Simulation, Modeling, and Programming for Autonomous Robots, SIMPAR 2012, held in Tsukuba, Japan, in November 2012. The 33 revised full papers and presented together with 3 invited talks were carefully reviewed and selected from 46 submissions. Ten papers describe design of complex behaviors of autonomous  robots, 9 address software layers,  8 papers  refer to related modeling and learning. The papers are organized in topical sections on mobile robots, software modeling and architecture and humanoid and biped robots.